Assessing Of Parameters Of Energy Supply Systems Of Mobile Homes Based On Renewable Energy Sources (Texas Journal of Engineering and Technology, 2025)
In this article, the research of fuel energy supply systems of mobile homes based on alternative energy sources, as well as the possibility of obtaining liquid, solid and gaseous alternative fuels from the proposed combined pyrolysis - biogas device, and the use in autonomous heating systems of mobile homes, which are energetically and economically effective that it can be useful for different groups of people and situations, mobile homes provide comfortable and convenient living in steppe and desert areas, mobile home Fuel systems in a mobile home use a biogas plant and electricity from the main electrical panel. It is described as being similar to a traditional home with circuits, wires, sockets and switches